Europe, globalization and crisis. From integrationto disillusionment - Parra, Néstor Hernando (Universidad Pedagógica y Tecnológica de Colombia, 2013)
The processes of integration of the European countries that have been characterized by their solidity and stability, have been broken for a series of events of political, social and economic character, reflected by the crisis affecting the European Union in the last years. The role of the European Union as central entity in the reconstruction of the Old Continent after long decades of decadence and destruction product of two world wars and many post-conflict, has been weakening on a larger scale with the passage of time, due to the processes of globalization which are occurring in the world. The analysis of this crisis cannot be given without bearing in mind the globalization as the element that has allowed constructing the universal network. Globalization that in Europe identifies with the threats to the survival of the Nation-State; to the Euro as international currency and currency of seventeen countries; to the European Union as supranational block; to the European model of life made concrete in the State of Well-being; to the quality of life of its peoples; to the unwanted set back of great part of the new middle class; and, with intimate pain, to the future of its new generations. Big surprise, because until the end of the 20th century it was recognized that the biggest victims of neoliberal globalization, were, until that moment, the developing countries.